2012
DOI: 10.1002/mrm.24284
|View full text |Cite
|
Sign up to set email alerts
|

A new method for detecting exchanging amide protons using chemical exchange rotation transfer

Abstract: In this study, we introduce a new method for amide proton transfer imaging based on chemical exchange rotation transfer. It avoids several artifacts that plague conventional chemical exchange saturation transfer approaches by creating label and reference scans based on varying the irradiation pulse rotation angle (π and 2π radians) instead of the frequency offset (3.5 and −3.5 ppm). Specifically, conventional analysis is sensitive to confounding contributions from magnetic field (B0) inhomogeneities and, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(171 citation statements)
references
References 45 publications
5
165
1
Order By: Relevance
“…Finally, the standard APTW metric based on the MTR asymmetry analysis could be subject to contamination by the upfield nuclear Overhauser enhancement and other effects. To more accurately quantify the APT effect, a more complicated APT imaging acquisition [34, 35] or analysis [36-38] approach may be used in the future. However, it has been demonstrated recently that the MTR asymmetry at 3.5 ppm remains a valid metric for APT imaging at 3 T (clinical B 0 field strengths) and 4.7 T [38].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the standard APTW metric based on the MTR asymmetry analysis could be subject to contamination by the upfield nuclear Overhauser enhancement and other effects. To more accurately quantify the APT effect, a more complicated APT imaging acquisition [34, 35] or analysis [36-38] approach may be used in the future. However, it has been demonstrated recently that the MTR asymmetry at 3.5 ppm remains a valid metric for APT imaging at 3 T (clinical B 0 field strengths) and 4.7 T [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that for dilute CEST agents undergoing slow chemical exchange, pulse-train CEST MRI provides similar CEST effect as the CW-CEST MRI. Because the typical CEST effect is only a few percent, it is important to optimize pulse-train CEST MRI for in vivo applications (Sun et al , 2011a; Wu et al , 2012; Tee et al , 2013; Yuan et al , 2013; Sun et al , 2013b; Sun et al , 2014a; Sun et al , 2014b; Zhu et al , 2010; Shah et al , 2011; Zu et al , 2013). However, because of the long computation time it takes to simulate pulse-train CEST MRI, it remains challenging to fit pulse-train CEST MRI measurements and solve the underlying CEST system.…”
Section: Introductionmentioning
confidence: 99%
“…Such investigation would have required modeling of complex lineshapes to disentangle the contributions of ihMT to MT-asymmetry and vice versa, as well as a full treatment of MT-asymmetry in the proposed experimental set-up. In particular, factors complicating the CEST signal, such as water direct saturation at different offsets, effects of RF pulse bandwidths and flip angles [34], should have been precisely analyzed.…”
Section: General Observationsmentioning
confidence: 99%